KESEJAHTERAAN PEMEGANG SAHAMBIDDER DALAM JANGKA PANJANG PASCA MERGER DAN AKUISISI - Pratiwi, Permata Dian (Optimum: Jurnal Ekonomi dan Pembangunan, 2016)
The purpose of thisresearch is to fi nd how merger and acquisition create value for stakeholder at long-term post of an event. Testing of this welfare cannot be measured only in the short-term to avoid the bubble effect. Merger and acquisition conducted to obtain benefi ts or synergies. So the hypothesis proposed in this study is there a statistically signifi cant positive value for bidding after the merger in the long-term. But the results of this study indicate that the fallout. The result showed statistically signifi cant that the merger and acquisition do not provide for the welfare of shareholders bidder after the merger in the long-term. The research result supports several previous studies.